Improving Student’s Critical Thinking Skills Through Social Interaction With The School Environment By Implementing A Guided Inquiry Model Based On Outdoor Learning In Science Learning In Elementary Schools - Lutfiah Nur Ahmad; Sunardin (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
This study aims to improve the critical thinking skills of fifth grade students of SDN 33 Kalukulajuk, Palopo City in science learning through a guided inquiry model based on outdoor learning. This study is motivated by the low critical thinking skills of students and the dominance of learning that takes place in the classroom so that students are less able to obtain contextual and meaningful learning experiences. Although various previous studies have shown that the guided inquiry model is effective in improving critical thinking, most studies still focus on the application of guided inquiry in general or in other subjects, so there has not been much study of the integration of guided inquiry with outdoor learning specifically in science learning in elementary schools. The novelty of this study lies in the integration of the guided inquiry model with outdoor learning as an approach that not only emphasizes cognitive processes, but also direct learning experiences, social interactions, and students' connectedness to the real environment. This study is a Classroom Action Research with a Kurt Lewin design that was carried out in two cycles on 28 fifth grade students consisting of 14 girls and 14 boys. Data were obtained through observations of learning implementation, observations of student activities, and critical thinking essay tests. The results of the study showed an increase in the implementation of learning from 82 to 91, student activity from 77 to 89, and the completion of critical thinking skills from 14 to 86. Thus, the guided inquiry model based on outdoor learning is effective in improving students' critical thinking skills in science learning.